Els aplecs «ts» i «dz» en valencià. Una anàlisi des de la teoria de l'optimitat - Jiménez, Jesús (Caplletra. Revista Internacional de Filologia, 2015)
This article intends to demonstrate that the final form of the clusters /ts/ and /dz/ in the Valencian dialect depends upon the behaviour of a series of universal principles referring to the syllabic structure. The author assumes that such restrictions are ranked on a language particular basis, according to the postulates of Optimality Theory (Prince & Smolensky 1993). Then, the outputs for the alveolar clusters will be the result of applying the constraint hierarchy to the set of possible candidates consistent with every input. The different results of the clusters /ts/ and /dz/ in Valencian, and this dialect' s divergences from other Catalan varieties are explained by the differences in the ranking of the principles which each variety presents.